1980
DOI: 10.1007/bf01205229
|View full text |Cite
|
Sign up to set email alerts
|

A freeze-fracture study of synaptic junction development in the superficial layers of the chick optic tectum

Abstract: Synaptogenesis in the superficial layers of the rostral pole of the chick optic tectum has been studied using freeze-fracture techniques. The developmental sequence of intramembrane organization at synaptic junctions involves the accumulation and assembly of intramembrane particles into aggregates characteristic of the mature junctions. By embryonic day seven, areas of loosely-arranged clusters of medium-sized particles are observed on the cytoplasmic membrane leaflets (P-faces) of developing neurites. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The size of the receptor matrix in relation to that of the postsynaptic differentiation is quite difficult to assess, mainly because of the hazy border of this structure; but we consistently find with immunogold labeling that receptors extend slightly beyond the limits of the synaptic complex, this situation being appropriate for exocytotic events occurring at the periphery of the active zone. In any case, the high concentration of receptors in front of the active zone is compatible with the notion that particles observed by cryofracture to be aggregated at the level of the postsynaptic density are receptors for neurotransmitters (10,17). This concept was primarily based on evidence that, at the electroplaque, postsynaptic intramembrane particles are receptor proteins and/or ion channels (12).…”
Section: Extension Of the Receptor Matrixsupporting
confidence: 52%
“…The size of the receptor matrix in relation to that of the postsynaptic differentiation is quite difficult to assess, mainly because of the hazy border of this structure; but we consistently find with immunogold labeling that receptors extend slightly beyond the limits of the synaptic complex, this situation being appropriate for exocytotic events occurring at the periphery of the active zone. In any case, the high concentration of receptors in front of the active zone is compatible with the notion that particles observed by cryofracture to be aggregated at the level of the postsynaptic density are receptors for neurotransmitters (10,17). This concept was primarily based on evidence that, at the electroplaque, postsynaptic intramembrane particles are receptor proteins and/or ion channels (12).…”
Section: Extension Of the Receptor Matrixsupporting
confidence: 52%
“…Rager and colleagues reported that the first morphological contacts can be observed in the stratum griseum et fibrosum superficiale (SGFS) near the area centralis of the tectum at E10–E11, and that the electrically evoked EPSP can also first be detected on the same day (Rager, 1976b; Rager & Kreische, 1978). By contrast, McGraw et al . (1980) reported that immature retinotectal synaptic contacts can be found by ultrastructural study of the rostral pole of the tectum at E8.…”
Section: Comparison Between the Epsp Pattern And Morphologically Detementioning
confidence: 89%
“…The ‘rostroventral pole of the tectum’, in which McGraw et al . (1980) and McLoon (1985) observed the first morphological retinotectal synaptic connections at E8 and E7, respectively, partly overlaps with the area we termed the ‘tecto/tegmental region’ in the present study.…”
Section: Comparison Between the Epsp Pattern And Morphologically Detementioning
confidence: 99%
See 1 more Smart Citation
“…Additional support comes from thin sections through comparable regions, in which fusing coated vesicles are frequently observed in continuity with the presynaptic membrane. Coated vesicles have been implicated in synaptogenesis in a number of studies which have demonstrated coated vesicles fusing with the postsynaptic plasmalemma at or adjacent to sites of developing presynaptic contacts (Altman 1971;Stelzner et al, 1973;Hinds & Hinds, 1976;Rees et aI., 1976;McGraw et al, 1980). Rees et al (1976) (see also Rees, 1978) have suggested that coated vesicles may be involved in the transport of specialized material from the Golgi apparatus to the sites of future synaptic contacts, whereby the material initially plays a part in the formation of the synapse and later in the adhesion of synaptic processes and formation of the mature active zone.…”
Section: Discussionmentioning
confidence: 98%